Complex intervention programme to improve patient safety and facilitate deprescribing in frail older patients living at home (COFRAIL): A process evaluation of a cluster randomised controlled trial - Jens Abraham; Steffen Fleischer; Achim Mortsiefer; Eva Drewelow; Manuela Ritzke; Birgitt Wiese; Charalabos Markos Dintsios; Veronika Bencheva; Petra Thürmann; Stefan Wilm; Gabriele Meyer (PLoS ONE, 2026)
Introduction Frailty is associated with negative health outcomes in geriatric patients. A large proportion of frail patients is affected by polypharmacy, which in turn may be a possible cause of frailty. The cluster randomised controlled COFRAIL trial investigated the effects of family conferences to improve the care of frail patients. Deprescribing and communication about prioritising health goals between patients, relatives and general practitioners were key components of the intervention. An accompanying process evaluation was conducted to investigate whether the study intervention was implemented as intended and to describe the experiences of the target groups. Methods The process evaluation took place between February 2019 and October 2021 and followed international guidelines. Process parameters were collected using study documentation, standardised questionnaires and guided telephone interviews with a convenience sample of patients, relatives and general practitioners. Quantitative data were analysed descriptively, qualitative data through content analysis. Results Almost all general practitioners in the intervention group completed both mandatory trainings. Overall, 68% of the patients took part in all three planned family conferences, 85% in at least two. Patients, relatives and general practitioners reported positive experiences with the family conferences. Patients and relatives felt involved in the decision-making process and had predominantly no concerns when medication was discontinued. Only a few general practitioners considered the implementation of family conferences in regular care to be impractical. A supportive pharmacological hotline was not utilised frequently by the general practitioners. Due to the SARS-CoV-2 pandemic, some study procedures were adapted but did not have any negative impact. Conclusions While the COFRAIL study did not achieve its primary goals, we identified no major barriers in the implementation of the intervention programme. Overall, the target groups experienced the approach of family conferences positively. However, the process evaluation provides valuable lessons for designing and implementing similar interventions in the future.